Conservation Benefits of Marine Reserves are Undiminished Near Coastal Rivers and Cities. Issue 5 (19th September 2014) - Huijbers, Chantal M.; Connolly, Rod M.; Pitt, Kylie A.; Schoeman, David S.; Schlacher, Thomas A.; Burfeind, Dana D.; Steele, Chantel; Olds, Andrew D.; Maxwell, Paul S.; Babcock, Russell C.; Rissik, David
Abstract: Recent assessments of marine reserves have emphasized the importance of socio‐economic factors in reserve performance. Debates continue, however, about whether we should avoid or promote the placement of reserves near potentially detrimental forces, including coastal cities or rivers. We performed a global meta‐analysis to test whether proximity to major coastal influences affected the ability of marine reserves to enhance the abundance of organisms relative to surrounding areas. A strong effect of reserve performance was evident for a range of trophic groups. Positive effects of reserves were undiminished by proximity to coastal cities or river discharges for the majority of taxonomic groups under conservation. We conclude that reserves placed in coastal areas are likely to protect marine populations to a similar extent as reserves in remote or less‐developed locations. Marine reserves in coastal settings can be an important tool to protect species and ecosystems in places threatened by human activities.